Entrepreneurship development through food processing - Tewari, Pratibha; Singhal, Savita; Kalash, Poonam; Jain, Dilip (Indian Farming, 2018)
In the recent past enhanced food grains and horticultural production opened massive opportunities in entrepreneurial development in agroprocessing sector. As the farmer distress is surmounting every day, agriculture needs multi-level support through research and development, enhancement in facility of cold storage and ware houses, strong market support, capacity development of women/youth and other stakeholders. Food processing sector is acclaimed as rising venture of agro-processing industries in India. Value-added products developed from lesser known naturally occurring plant sources of Indian arid region holds promise for sustained livelihood options through entrepreneurship development.